ANALISIS YURIDIS PENGGUNAAN SMART CONTRACT DALAM PERSPEKTIF ASAS KEBEBASAN BERKONTRAK - Andini Eka Budiyanto (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Smart contracts as a blockchain-based technological innovation invite juridical analysis in the context of the principle of freedom of contract. This research examines the impact of the use of smart contracts on the principle of freedom of contract, which emphasizes the rights and obligations of parties entering into an agreement or contract to determine the terms of the agreement without interference from third parties. Smart contracts provide the possibility of automating contract execution, increasing efficiency and transparency. The displacement of a notary as an official authorized to ratify a deed of agreement or contract raises big questions in this smart contract. Juridical analysis focuses on how these technologies affect the balance between freedom of contract and legal protection against breach of contract. If a contract breach occurs at a later date, will it give rise to legal consequences if it harms one of the parties and what protection can be given to the party who feels disadvantaged? The aspect of legal uncertainty regarding the existence of smart contracts is highlighted in this research, taking into account the complexity of law enforcement and protecting the rights of those making agreements or contracts. This study is interesting to discuss because technology is increasingly developing into the realm of law, but the problem is how the law itself responds to these technological changes. Will the law facilitate or even reject it? In essence, the use of smart contracts opens up new but challenging opportunities in understanding the role of the principle of freedom of contract in the era of advanced technology. Evolving legal and regulatory implications are a critical focus for ensuring continuity between technological innovation and the legal principles underlying it.